2019
DOI: 10.3390/agriculture9050102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Species, Fertilization and Harvest Date on Microbial Composition and Mycotoxin Content in Forage

Abstract: The aim of the project was to evaluate the potential of microbial threat to feed safety in the year 2018. Analyses of the epiphytic community of several forage species (clovers, cocksfoot, fescue, festulolium, perennial ryegrass, timothy and trefoil) in variants of fertilized and non-fertilized vegetation were performed. The hypothesis is based on the fact that microorganisms are normally present on plant material during its growth all the way from the seed to the senescence; they are influenced by a plant’s f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…However, this effect was significant in the next year of observation; therefore, it is possible to assume that the year has a greater impact on mycotoxin concentration in the biomass than fertilization. Similarly, in the study by Baholet et al, no differences in DON levels were found with an increased digestate dose [58]. This was also demonstrated in our study, where an increased digestate dose did not significantly affect DON, AFB1, or T-2 levels (p < 0.05; Table 6).…”
Section: Discussionsupporting
confidence: 91%
“…However, this effect was significant in the next year of observation; therefore, it is possible to assume that the year has a greater impact on mycotoxin concentration in the biomass than fertilization. Similarly, in the study by Baholet et al, no differences in DON levels were found with an increased digestate dose [58]. This was also demonstrated in our study, where an increased digestate dose did not significantly affect DON, AFB1, or T-2 levels (p < 0.05; Table 6).…”
Section: Discussionsupporting
confidence: 91%
“…The common and unique OTUs was used to construct the Venn diagram by R (version 1.6.2). The alpha diversity for these samples were used the Chao1 value and Shannon index to evaluate richness and diversity [17][18][19][20], and Good's coverage were calculated through QIIME software. Principal coordinates analysis (PCoA) was conducted on OTU level by R (version 3.3.1) software based on weighted UniFrac distances.…”
Section: Bioinformatics and Statistical Analysismentioning
confidence: 99%
“…Pre- and post-harvest mitigation strategies, including good farming practice (GFP), good agricultural practice (GAP), and good handling practice (GHP) [ 75 ], mainly used to prevent mycotoxins contamination are the most promising because they are cost-effective and easy to use by farmers. Besides, proper fertilization [ 111 ], selection of disease-resistant breeding [ 112 ], cropping rotation systems [ 113 ], use of fungicides/pesticides, insects control measures, proper drying, appropriate storage, and transportation are encouraged. In addition, physical sorting methods, performed by removing damaged products based on quality parameters such as color, size, shape, density, and visible fungal growth [ 110 ], are also known to have the potential to reduce the impacts of both mold infection and mycotoxins contamination.…”
Section: Mycotoxin Management Strategiesmentioning
confidence: 99%